2019
DOI: 10.1016/j.jcmg.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Global Longitudinal Strain in Hypertrophic Cardiomyopathy

Abstract: Our systematic review of more than 3000 HCM patients suggests an association of abnormal LV-GLS with adverse composite cardiac outcomes and ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 33 publications
4
64
1
1
Order By: Relevance
“…An overlap with the phenotype of LV non-compaction (LVNC) is being discussed. Abnormal global longitudinal strain is a marker for an impaired prognosis [ 246 ].…”
Section: Myocarditis and Other Cardiomyopathiesmentioning
confidence: 99%
“…An overlap with the phenotype of LV non-compaction (LVNC) is being discussed. Abnormal global longitudinal strain is a marker for an impaired prognosis [ 246 ].…”
Section: Myocarditis and Other Cardiomyopathiesmentioning
confidence: 99%
“…Currently, left ventricular global longitudinal strain (GLS) using speckle tracking echocardiography is the most ubiquitously used strain parameter in HCM (online supplementary figure 2). 39 In a recent systemic review of 14 observational studies in patients with HCM (n=3154), we found a clear association between abnormal LV GLS with adverse cardiac outcomes including mortality, appropriate ICD discharge and ventricular arrhythmias. A barrier to the routine use of LV GLS for clinical decision making is the lack of prospective evaluations to confirm its utility in HCM 39.…”
Section: Introductionmentioning
confidence: 78%
“…39 In a recent systemic review of 14 observational studies in patients with HCM (n=3154), we found a clear association between abnormal LV GLS with adverse cardiac outcomes including mortality, appropriate ICD discharge and ventricular arrhythmias. A barrier to the routine use of LV GLS for clinical decision making is the lack of prospective evaluations to confirm its utility in HCM 39. Furthermore, there are variations in the normal reference ranges in part contributed by the lack of standardisation between various echocardiography platforms.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Beside well-established echocardiographic risk factors, there are novel echo parameters derived from 2D STE analysis that may provide additional insight in SCD risk stratification. In a study on more than 3000 HCM patients, abnormal GLS was associated with VA [48]. Mechanical dispersion (i.e., the standard deviation of the time from the onset of systole to maximum contraction for each of the myocardial segments, an expression of heterogeneous contraction and electrical activation) relates to the extent of fibrosis (assessed by CMR) and is an independent predictor of VA (Fig.…”
Section: Assessing the Risk Of Sudden Cardiac Deathmentioning
confidence: 99%